Hubungan Antara Status Gizi dengan Kondisi Fisik Atlet pada Pemain Sepak Bola Putra Usia 10-12 Tahun Klub SSB Putra Asri Gemolong - Wisnu Mahardika (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
The purpose of this study was to determine the relationship between nutritional status and the physical condition of athletes in male soccer players aged 10-12 years at the SSB Putra Asri Gemolong club. The research method used is the correlational method. This research was conducted at SSB Putra Asri Gemolong and this research was carried out from August to September 2022. The sample for this research was 30 people. Data collection techniques in this study used tests and measurements. Quantitative data analysis was assisted by the SPSS application version 25. The results showed that tests of nutritional status and physical condition of athletes on male soccer players aged 10-12 years at the SSB Putra Asri Gemolong 2022 club, namely the nutritional status test showed a "poor" classification of 10%. (3 athletes), "poor" 26% (8 athletes), while "good" 63% (19 athletes). On the physical condition test the classification was "less" 43.3% (13 athletes), "less" 30% (9 athletes), "currently" 26.7% (8 athletes). Based on the results of the research and the results of the data analysis that has been carried out, it can be concluded that there is no significant relationship between nutritional status and the physical condition of athletes in SSB Men's football players aged 10-12 Years Asri Gemolong Boys Club in 2022, with a significance value of 0.946 > 0 ,05. When viewed from the guidelines for the degree of association, the degree of association between nutritional status and physical condition shows that there is no correlation level of 0.013. According to the guideline table, the Pearson correlation value of 0.00 to 0.60 has no correlation. Keywords: Football, Nutritional Status, Physical Condition,